Ceftriaxone Combined With Metronidazole is Superior to Cefoxitin Alone in the Management of Uncomplicated Appendicitis in Children: Results from a Multicenter Collaborative Comparative Effectiveness Study. Issue 6 (December 2021) - Kashtan, Mark A.; Graham, Dionne A.; Melvin, Patrice; Cameron, Danielle B.; Anandalwar, Seema P.; Hills-Dunlap, Jonathan L.; Rangel, Shawn J.
Abstract : Objective: To compare rates of surgical site infection between the 2 most commonly utilized narrow-spectrum antibiotic regimens in children with uncomplicated appendicitis (ceftriaxone with metronidazole and cefoxitin alone). Summary of Background Data: Narrow-spectrum antibiotics have been found to be equivalent to extended-spectrum (antipseudomonal) agents in preventing surgical site infection (SSI) in children with uncomplicated appendicitis. The comparative effectiveness of different narrow-spectrum agents has not been reported. Methods: This was a multicenter retrospective cohort study using clinical data from the Pediatric National Surgical Quality Improvement Program Appendectomy Collaborative Pilot database merged with antibiotic utilization data from the Pediatric Health Information System database from January 2013 to June 2015. Multivariable logistic regression was used to compare outcomes between antibiotic treatment groups after adjusting for patient characteristics, surrogate measures of disease severity, and clustering of outcomes within hospitals. Results: Eight hundred forty-six patients from 14 hospitals were included in the final study cohort with an overall SSI rate of 1.3%. A total of 56.0% of patients received ceftriaxone with metronidazole (hospital range: 0%–100%) and 44.0% received cefoxitin (range: 0%–100%). In the multivariable model, ceftriaxone with metronidazole was associated with a 90% reduction in the odds of a SSI compared to cefoxitin [0.2% vs 2.7%; odds ratio: 0.10 (95% confidence interval 0.02–0.60); P = 0.01]. Conclusions: Ceftriaxone combined with metronidazole is superior to cefoxitin alone in preventing SSIs in children with uncomplicated appendicitis.